The role of viscosity on skin penetration from cellulose ether‐based hydrogels - Binder, Lisa; Mazál, Julia; Petz, Romana; Klang, Victoria; Valenta, Claudia (Skin research and technology, 2019)
Background The rheological properties of dermal drug delivery systems are of importance when designing new formulations. Viscosity not only affects features such as spreadability and skin feel, but may also affect the skin penetration of incorporated actives. Data on the latter aspect are controversial. Our objective was to elucidate the relation between viscosity and drug delivery performance of different model hydrogels assuming that enhanced microviscosity might delay drug release and penetration. Materials and Methods Hydrogels covering a broad viscosity range were prepared by adding either HPMC or HEC as gelling agents in different concentrations. To investigate the ability of the gels to deliver a model drug into the skin, sulphadiazine sodium was incorporated and its in vitro skin penetration was monitored using tape stripping/HPLC analysis and non‐invasive confocal Raman spectroscopy. Results The trends observed with the two different experimental setups were comparable. Drug penetration depths decreased slightly with increasing viscosity, suggesting slower drug release due to the increasingly dense gel networks. However, the total penetrated drug amounts were independent of the exact formulation viscosity. Conclusion Drug penetration was largely unaffected by hydrogel viscosity. Moderately enhanced viscosity is advisable when designing cellulose ether hydrogels to allow for convenient application.